Non-Residential CAT Communities 2015 - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
A brochure describing Non-residential Connecting Across Topics (CAT) Communities at Kansas State University for the 2015-2016 academic year. Provided in the brochure are descriptions of the Pre-Professional CAT Communities, Interest-Based CAT Communities, and Study Abroad CAT Communities, as well as a brief overview of how CAT Communities operate.
Keywords: Guide; CAT communities; First-year experience program; Learning Assistants; Fliers (printed matter)